2014
DOI: 10.1002/chir.22393
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Stereochemical Study, and Cytotoxic Activity of Isobenzofuran Derivatives From a Marine Streptomyces sp.

Abstract: A new 1,3-dihydroisobenzofuran derivative (), together with its epimer (), was isolated from marine Streptomyces sp. W007. The structure of the two compounds was established by extensive spectroscopic analysis and comparison with reported data. The absolute configurations of and were determined by a combination of experimental and computational means, including J-coupling analysis and nuclear Overhauser effect spectroscopy (NOESY) spectra, nuclear magnetic resonance (NMR) calculations, electronic circular dich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…20) In 2015, Shen and colleagues also isolated a compound with identical spectral data to Xie's 2012-isomer (6) from Streptomyces sp. CB01913 and suggested that the H-9/H-16 configuration of the 2012-isomer had to be revised as trans.…”
Section: )mentioning
confidence: 98%
See 2 more Smart Citations
“…20) In 2015, Shen and colleagues also isolated a compound with identical spectral data to Xie's 2012-isomer (6) from Streptomyces sp. CB01913 and suggested that the H-9/H-16 configuration of the 2012-isomer had to be revised as trans.…”
Section: )mentioning
confidence: 98%
“…W007 in 2012, 19) and also isolated an epimer of the 1,3-dihydroisobenzofuran in 2015 (=2015-isomer). 20) The first 1,3-dihydroisobenzofuran isolated in 2012 (=2012-isomer) was initially proposed to have a cis H-9/H-16 configuration.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also supported by comparing its spectral data with the known related (-)- 1,4-dimethoxy-3-(3′-hydroxy-3′-methyl-1′-tetralone)-1(3H)-isobenzofuran. 21 HMBC correlations from H-3 to C-7′ through 3 J coupling revealed the connectivity of the 1,3-dihydroisobenzofuran fragment to C-8′ of the tetralone moiety. The relative configuration of 1 was assigned by an analysis of the NOESY spectrum and proton coupling constants ( Table 1).…”
Section: Introductionmentioning
confidence: 98%
“…The MW of the mixture was 350 Daltons based on (+)-ESIMS. The molecular formula was estimated to be C 21 revealed one oxygenated methine proton, two methoxy groups, and one methyl signal. The 13 C NMR data (Table 2) of 3 and 4 showed seven aromatic methines, eleven quaternary carbon atoms, two methoxy groups, and one methyl carbon.…”
Section: Introductionmentioning
confidence: 99%